Use of Fly Ash for Improvement of Bond Strength with Different Development Lengths - Hamza Umar; Muhammad Haseeb Zaheer; Umar Saeed; Muhammad Aun Niaz; Aftab Ahmed (Journal of ICT, Design, Engineering and Technological Science, 2022)
The goal of this research is to explore the feasibility of using fly ash concrete for structural applications by testing the material’s reinforcement bond properties. A pull-out test was performed on specimens with a 0, 20, 25, and 30 percent fly ash replacement of cement and then compared to identical tests performed on control specimens cast from a 100 percent Portland cement mix. The pull-out tests were performed on specimens with 12 mm, 20mm, and 25 mm steel bars used. Also, a compressive test was performed on specimens with 0, 20, 25, and 30 percent fly ash with the replacement of cement. As the fly ash percentage increases the slump value decreases. This creates problems in the workability of the concrete. When the slump decreases, then increase the strength of the concrete. As compared to normal concrete specimens tests performed with 100 percent ordinary Portland cement the use of 20, 25, and 30 percent results in an increase in both compressive and bond strength.